PENGARUH LEVERAGE, AKTIVITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Sektor Energi Yang Terdaftar di Bursa Efek Indonesia Tahun 2019–2023) - Fikri, Sofi Nabila; Indrabudiman, Amir (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This research was conducted with the aim of determining the influence of Leverage, Activity, Profitability and Company Size on in Energy Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period. The sampling technique in this research used purposive sampling with a sample of 49 Energy Sectors listed on the Indonesian Stock Exchange that met the sample criteria. The data analysis used in this research is multiple linear regression analysis using statistical testing tools, namely SPSS version 22.0. Based on the research results, it can be concluded that Leverage have a significant positive effect on financial distres. Meanwhile Activity, Profitability and Company Size have a significant negative effect on Finacial Distress.